2020
DOI: 10.3390/genes12010049
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Integrated Genetic Map of the Complete Karyotype of Solea senegalensis (Kaup 1858)

Abstract: Solea senegalensis aquaculture production has experienced a great increase in the last decade and, consequently, the genome knowledge of the species is gaining attention. In this sense, obtaining a high-density genome mapping of the species could offer clues to the aquaculture improvement in those aspects not resolved so far. In the present article, a review and new processed data have allowed to obtain a high-density BAC-based cytogenetic map of S. senegalensis beside the analysis of the sequences of such BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The solution was filtered (mesh size 40 to 100 μm), subjected to a hypotonic shock with KCl and fixed in Carnoy solution. Positive BAC clones were isolated following Merlo et al (2021) and labelled either by nick translation (García-Cegarra et al, 2013) or by DOP-PCR (Portela-Bens et al, 2017). Pre-treatment, hybridization, post-hybridization and staining for double-fluorescence in situ hybridization (FISH) followed García-Cegarra et al (2013) and for multiple-FISH Portela-Bens et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution was filtered (mesh size 40 to 100 μm), subjected to a hypotonic shock with KCl and fixed in Carnoy solution. Positive BAC clones were isolated following Merlo et al (2021) and labelled either by nick translation (García-Cegarra et al, 2013) or by DOP-PCR (Portela-Bens et al, 2017). Pre-treatment, hybridization, post-hybridization and staining for double-fluorescence in situ hybridization (FISH) followed García-Cegarra et al (2013) and for multiple-FISH Portela-Bens et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…BAC clones were sequenced using either a Genome Sequencing FLX System or MiSeq Illumina by the LifesequencingTM Platform (Valencia, Spain). Assembly, functional and structural annotation of BAC sequences was carried out as previously reported (Merlo et al, 2021).…”
Section: Cytogenetic Map and Mapping Integrationmentioning
confidence: 99%
“…There is also the case of the Senegal sole Solea senegalensis , for which a comprehensive integrated genetic map of the complete karyotype was presented. These data on the genome organization support the existence of a sex proto-chromosome pair and show that Robertsonian fusions and chromosomal inversions drive the evolution of the karyotype of this species, demonstrating the existence of conserved gene linkages shared with other fish model species [ 25 ]. Other examples concern Salmonid species.…”
mentioning
confidence: 69%
“…Unfortunately, there has been no unambiguous numbering and naming for all the chromosomes of C. farreri due to the lack of accurate chromosomal markers. In some species, such as sorghum (Kim et al, 2002(Kim et al, , 2005, silkworm (Yoshido et al, 2005), alpaca (Mendoza et al, 2020), and Senegalese sole (Merlo et al, 2021), all chromosomes could be identified by simultaneous FISH of a cocktail of landed large-insert DNA clones and/or repetitive DNA probes. In this study, we successfully distinguished all the 19 chromosomes of C. farreri through multiple two-color FISH and numbered them based on the chromosome-specific markers aided by the chromosomal morphology and lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The development of fluorescence in situ hybridization (FISH) is a significant step toward chromosome identification, and FISH is a well-established approach for determining the location and relative order of DNA sequences in chromosomes (Zhang et al, 2008a;Merlo et al, 2021). The initial probes used as landmarks for chromosome distinguish were repetitive sequences, mainly including satellite sequences (Wang et al, 2001;Zhang et al, 2008a), ribosomal DNA (Zhang et al, 1999;Xu et al, 2001;Huang et al, 2007a,b), and histone genes (Eirín-López et al, 2002Zhang et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%